Hole-injection role of solution-processed thermally treated VOx thin films in Si nanowire-based solar cells. (August 2022) - Abdelhameed, Mohammed; Abdelbar, Mostafa F.; Esmat, Mohamed; Jevasuwan, Wipakorn; Fukata, Naoki
Abstract: We have studied the hole-injection workability of dopant-free vanadium oxide (VOx ) semiconductor thin films. Solution-processable VOx films were annealed in different atmospheres at 450 ˚C. X-ray diffraction showed that different crystal structures of V2 O5, VO2 (M) and VO2 (B) were obtained after annealing in oxygen, nitrogen and under vacuum respectively. Gap states that originated from oxygen deficiencies located inside the band gap of the annealed VOx were demonstrated using X-ray photoelectron spectroscopy. These VOx thin films act effectively as transparent hole-injection layers owing to their high work function, wide band gap, and presence of oxygen deficiencies. The different ambient annealed VOx films were employed in Si nanowire (SiNW)-based solar cells. The vacuum-annealed oxide film VO2–x (B) showed the best hole-injection ability. SiNWs/VOx solar cells are noticeably more stable than SiNWs/PEDOT:PSS hybrid solar cells, which decay swiftly under ambient conditions unless encapsulation is provided. The utilization of VOx films to act as hole-injection layers opens a pathway toward the development of cheap and durable electronics and optoelectronics devices. Graphical Abstract: Cathode/SiNWs/VOx /anode solar cells revealed the hole-injection role of the VOx layer, which in turn facilitates the photogenerated carriers' separation and collection, due to the presence of oxygen deficiencies. It also exhibited better stability than those employing PEDOT:PSS films. ga1 Highlights: Different VOx films with different crystal structures and stoichiometries were successfully formed on silicon substrates. Shallow defect states in VO2-x layers facilitate hole transport, resulting in improved conversion efficiency. The best performance was achieved with a solar cell exploiting a 15 nm-VOx layer annealed under vacuum at 400 ˚C. SiNWs/VOx solar cells are noticeably more stable than SiNWs/PEDOT:PSS hybrid solar cells.